2022
DOI: 10.1136/bmjresp-2022-001355
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among genetic variants, obesity traits and asthma in the Taiwan Biobank

Abstract: Background and objectiveObesity and asthma impose a heavy health and economic burden on millions of people around the world. The complex interaction between genetic traits and phenotypes caused the mechanism between obesity and asthma is still vague. This study investigates the relationship among obesity-related polygenic risk score (PRS), obesity phenotypes and the risk of having asthma.MethodsThis is a matched case–control study, with 4 controls (8288 non-asthmatic) for each case (2072 asthmatic). Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…There is little evidence of shared genetic correlation between BMI and early-onset asthma. In a recent case -control study using data from a Taiwan Biobank cohort, the obese phenotype was associated with a higher chance of developing asthma by approximately 26% [9]. Other independent risk factors for asthma included lower educational level and increased PM2.5 exposure.…”
Section: Genetic Evidence For Associationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little evidence of shared genetic correlation between BMI and early-onset asthma. In a recent case -control study using data from a Taiwan Biobank cohort, the obese phenotype was associated with a higher chance of developing asthma by approximately 26% [9]. Other independent risk factors for asthma included lower educational level and increased PM2.5 exposure.…”
Section: Genetic Evidence For Associationmentioning
confidence: 99%
“…A sedentary lifestyle as well as change in diet may have contributed to this increase [1,3,4]. Several epidemiological [4][5][6][7] and genetic [8][9][10] studies have shown a strong association between asthma and obesity although the direction of causality is still subject to debate [1]. In younger patients, asthma may lead to obesity due to lifestyle change and effect of corticosteroids, whereas in adult-onset asthma patients, obesity often precedes asthma [1].…”
Section: Introductionmentioning
confidence: 99%
“…This relationship between asthma and obesity can be explained by various different aspects including, but not limited to, duration of obesity [9], presence of significant co-morbids, common in utero conditions, and common predisposing dietary factors [13]. Furthermore, there is significant evidence that obesity and asthma may share the same genetic risk factors [14,15].…”
Section: Introductionmentioning
confidence: 99%